Perovskite active agent loaded coconut shell activated carbon composite material as well as preparation method and application thereof
By loading the perovskite active agent LaCo1-xMnxO3 on the coconut shell activated carbon, the perovskite active agent loaded coconut shell activated carbon composite material is solved, and the problems of limited and high cost of dyeing and printing wastewater treatment in the prior art are achieved, and high efficiency is achieved , environmentally friendly wastewater treatment effect.
Patent Information
- Application Number
- CN202411484921.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The prior art has limited effect when treating dyeing and printing wastewater, commercially available commercial activated carbon is costly and non-renewable, and the existing modified coconut shell activated carbon methods require additional power supply or complex raw material ratios, which are not suitable for large-scale industrial production.
The perovskite active agent LaCo1-xMnxO3 was prepared by sol-gel method, and it was loaded on coconut shell activated carbon by impregnation to form a perovskite active agent supported coconut shell activated carbon composite for efficient adsorption and catalytic degradation of printing and dyeing wastewater Malachite green dye in it.
It realizes efficient absorption and catalytic degradation of harmful dyes in printing and dyeing wastewater, reduces preparation costs, simplifies the process flow, is suitable for large-scale industrial production, and improves adsorption performance and environmentally friendly application value.
Smart Images

Figure CN119236963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid biomass waste recycling and biomass activated carbon preparation, and in particular to a perovskite activator-loaded coconut shell activated carbon composite material and a preparation method and application thereof. Background Art
[0002] With the acceleration of industrialization and environmental pollution, especially water pollution, the problem has become increasingly prominent. Among them, dyeing and printing wastewater has become an environmental problem that needs to be solved urgently due to its complex composition and high toxicity. Malachite green, which is common in dyeing and printing wastewater, is a triphenylmethane dye that poses a serious threat to aquatic life and human health. Traditional treatment methods are often limited in effect when treating such wastewater, while activated carbon adsorption has attracted widespread attention due to its advantages of high efficiency and no secondary pollution. However, the high cost and non-renewability of commercial activated carbon on the market limit its widespread application.
[0003] As an alternative to activated carbon, biochar has received widespread attention in the field of environmental remediation in recent years. Biochar carbon-based materials come from a wide range of sources, including rice husks, coconut shells, straw, livestock and poultry manure, sewage sludge and agricultural waste. These materials are not only low-cost but also renewable. Among them, coconut shells are ideal for preparing biochar due to their high yield, high cellulose content, low ash content and high mechanical lightness. Coconut shell activated carbon not only maintains the basic properties of activated carbon, such as high specific surface area and porous structure, but also exhibits better adsorption performance due to the special composition of coconut shells. In the prior art, CN202010173132 discloses a modified coconut shell activated carbon used as a three-dimensional electrode filling particle, and its preparation method and application. Activated carbon is prepared using coconut shell as the basic raw material, and modified coconut shell activated carbon is prepared using tetrabutyl titanate, isopropyl alcohol and nitric acid as modifiers. The modified coconut shell activated carbon with three-dimensional electrode-filled particles prepared by this method is used to treat organic wastewater and has the characteristics of low price, stable performance and good catalytic activity. However, in the process of treating organic wastewater, additional power is required for electrolysis, which consumes more energy and has certain limitations on its application scenarios.
[0004] In addition, CN107758789A discloses the preparation and application of a dyeing and printing wastewater treatment agent. Coconut shell powder is used as a raw material and is soaked and calcined with a phosphoric acid solution, and copper nitrate solution and cerium nitrate solution are used as modifiers to obtain modified coconut shell activated carbon by calcination, and then polyferric chloride, polyaluminium chloride and modified bentonite materials are added, mixed and granulated to obtain a wastewater treatment agent. This method can efficiently treat dyeing and printing wastewater, but its raw materials are diverse and the ratio is complex, which is not suitable for large-scale industrial production. Summary of the invention
[0005] In view of the deficiencies in the above-mentioned prior art, the present invention provides a composite material of coconut shell activated carbon loaded with a perovskite active agent, and a preparation method and application thereof. The present invention first uses La, Co and Mn metal salts as raw materials and adopts a sol-gel method to prepare a perovskite active agent; then uses coconut shell as a raw material to prepare activated carbon; and then loads the perovskite active agent on the coconut shell activated carbon by an impregnation method to obtain a composite material of coconut shell activated carbon loaded with a perovskite active agent. The preparation method of the present invention not only overcomes the problems in the prior art of requiring additional power for electrolysis, high requirements for raw material ratios and complex ratios, and being unsuitable for large-scale industrial production, but also realizes efficient absorption of malachite green harmful dyes in printing and dyeing wastewater, and has important research significance and environmental protection application value.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] The first object of the present invention is to provide a method for preparing a composite material of coconut shell activated carbon loaded with a perovskite active agent, comprising the following steps:
[0008] Coconut shell activated carbon is prepared using coconut shell as raw material.
[0009] The perovskite active agent LaCo is prepared by sol-gel method using La, Co and / or Mn metal salts as raw materials. 1-x Mn x O3, wherein the molar ratio of lanthanum, cobalt and manganese is 1:1-x:x, x is 0-1, that is, LaCoO3 and LaMnO3 are both suitable for the present invention.
[0010] LaCo 1-x Mn x O3 was loaded on coconut shell activated carbon to obtain a composite material of perovskite active agent loaded on coconut shell activated carbon. Malachite green was adsorbed by coconut shell activated carbon. LaCo 1-x Mn x O3 catalyzes the degradation of malachite green.
[0011] Preferably, in the perovskite active agent-loaded coconut shell activated carbon composite material, LaCo 1-x Mn x The mass percentage of O3 is 0.1wt% to 0.5wt%, and the perovskite active agent LaCo 1-x Mn x Too high a mass percentage of O3 will reduce the adsorption activity of the perovskite active agent loaded with coconut shell activated carbon composite material, deteriorate the adsorption performance, and increase the cost; the perovskite active agent LaCo 1-x Mn x If the mass percentage of O3 is too low, the adsorption activity and adsorption sites of the perovskite active agent loaded coconut shell activated carbon composite material will be reduced, resulting in poor adsorption performance.
[0012] Preferably, the particle size of coconut shell activated carbon is 60 mesh to 100 mesh, wherein a particle size that is too small will reduce the amount of perovskite loaded, and a particle size that is too large will increase the load and adsorption area, but the part that cannot be adsorbed in the center of the carbon particle becomes larger, which reduces the utilization rate of the coconut shell activated carbon.
[0013] Preferably, the loading method is: washing the coconut shell activated carbon with deionized water to remove surface impurities, and then drying to obtain treated coconut shell activated carbon; 1-x Mn x O3 is dispersed in deionized water to obtain LaCo 1-x Mn x O3 solution; LaCo 1-x Mn x O3 solution was impregnated onto the treated coconut shell activated carbon, and then LaCo 1-x Mn x O3 is attached to the surface of activated carbon and dried to obtain a perovskite active agent loaded coconut shell activated carbon composite material.
[0014] Preferably, coconut shell activated carbon is prepared according to the following steps: drying the coconut shell, and then heating it at 700° C. to 1000° C. for 30 min to 120 min in a protective atmosphere.
[0015] Preferably, LaCo 1-x Mn x O3 was prepared as follows:
[0016] Lanthanum nitrate hexahydrate, citric acid, cobalt nitrate hexahydrate and / or manganese nitrate are mixed in deionized water, and then the pH is adjusted to 8-9 with ammonia water to obtain a precursor solution; the precursor solution is heated and stirred at 80-90°C until a viscous gel is obtained; the gel is calcined at 730-780°C for 4h-6h to obtain LaCo 1-x Mn x O3.
[0017] The second object of the present invention is to provide a composite material of coconut shell activated carbon loaded with a perovskite active agent prepared by the above preparation method.
[0018] The third object of the present invention is to provide the use of the above-mentioned perovskite active agent loaded coconut shell activated carbon composite material in the preparation of malachite green treatment agent.
[0019] Preferably, the application method is: adding the perovskite active agent loaded coconut shell activated carbon composite material into the printing and dyeing wastewater, shaking and mixing, and using the perovskite active agent loaded coconut shell activated carbon composite material to adsorb and catalytically degrade malachite green in the printing and dyeing wastewater.
[0020] Preferably, the pH of the printing and dyeing wastewater is 4-10.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention provides a method for preparing a composite material of coconut shell activated carbon loaded with a perovskite active agent, wherein La, Co and / or Mn metal salts are used as raw materials, and a perovskite active agent LaCo is prepared by a sol-gel method. 1-x Mn x O3, activated carbon is prepared with coconut shell as raw material, and finally the perovskite active agent is loaded on the coconut shell activated carbon to obtain a perovskite active agent loaded coconut shell activated carbon composite material. The preparation method of the present invention not only overcomes the problems in the prior art that additional power is required for electrolysis, the preparation process is complicated, the raw material ratio requirement is high, and it is not suitable for large-scale industrial production, but also realizes the efficient absorption of malachite green harmful dyes in printing and dyeing wastewater, and has important research significance and environmental protection application value.
[0023] Among them, the main components of coconut shell include cellulose, hemicellulose and lignin. Lignin is a complex three-dimensional polymer network interwoven by phenylpropane units. Due to its high decomposition temperature of thermal polycondensation reaction, it has become a key component for manufacturing carbon materials. In addition, coconut shell has low ash content, high density, high mechanical strength, and forms a porous structure after carbonization, with high specific surface area and abundant micropores. At the same time, coconut shell activated carbon has the characteristics of renewability, low cost and environmental friendliness.
[0024] LaCo 1-x Mn x O3, as a perovskite oxide, has good catalytic activity. 1-x Mn x O3 loaded on coconut shell activated carbon can form a synergistic effect. On the one hand, the adsorption of coconut shell activated carbon can enrich the pollutant molecules in the wastewater, making them easier to be catalytically degraded by the perovskite active agent; on the other hand, the catalytic effect of the perovskite active agent can accelerate the degradation process of pollutants and improve the overall treatment efficiency. In addition, LaCo 1-x Mn x O3 has good chemical and thermal stability and can maintain its catalytic activity over a wide temperature and pH range.
[0025] Compared with the prior art, the perovskite active agent loaded coconut shell activated carbon composite material of the present invention utilizes waste biomass and reduces the preparation cost; the introduction of the perovskite active agent greatly improves the adsorption performance, the adsorption performance is better than similar products, and the preparation process is simple and the cycle life is long.
[0026] 2. The perovskite active agent loaded coconut shell activated carbon composite material of the present invention loads the perovskite active agent LaCo on the surface of the porous structure activated carbon 1-x Mnx O3, the perovskite active agent is formed by the accumulation of single crystal particles into a porous structure with complex channels, and there are active sites on the surface during the structure formation process. The composite porous structure design greatly increases the specific surface area of the composite material, expands the distribution range of the active sites, and effectively captures harmful molecules in printing and dyeing wastewater. It has excellent adsorption performance for malachite green harmful dyes in printing and dyeing wastewater.
[0027] 3. The present invention screens the conditions for the preparation of coconut shell activated carbon, adjusts the activation temperature and activation time, and effectively increases the adsorption capacity of malachite green by coconut shell activated carbon.
[0028] 4. The perovskite active agent loaded coconut shell activated carbon composite material prepared by the present invention has good adsorption performance for malachite green in printing and dyeing wastewater, and can effectively reduce the adsorption time of printing and dyeing wastewater. The main principles in the adsorption process are physical adsorption and chemical adsorption. Physical adsorption is determined by the specific surface area and pore distribution of coconut shell activated carbon. It has low adsorption heat, fast adsorption rate, reversible process and non-selective. Chemical adsorption is determined by the active sites on the pore surface of the perovskite active agent loaded coconut shell activated carbon composite material, and the chemical bonds dominated by polar forces, including electron sharing, transfer and decomposition of harmful molecules between the perovskite active agent loaded coconut shell activated carbon composite material and the harmful molecules in the printing and dyeing wastewater. Chemical adsorption usually only occurs in a single layer, has high heat absorption, shows selectivity, and is irreversible at room temperature, which makes the adsorption and desorption process of harmful molecules more complicated.
[0029] LaCo 1-x Mn x O3 is loaded on the surface of coconut shell activated carbon. When the loading amount does not reach the saturation point of its surface monolayer, the amorphous structure usually has a larger specific surface area and more active sites, which makes the perovskite active agent LaCo 1- x Mn x O3 is more fully in contact with coconut shell activated carbon, thereby improving the catalytic efficiency; and when the loading continues to increase and exceeds the saturation point of the monolayer on the surface of coconut shell activated carbon, the perovskite active agent LaCo 1-x Mn x O3 begins to form multilayer structures or aggregates on the surface of coconut shell activated carbon, resulting in LaCo 1-x Mn x The dispersion of O3 deteriorates, thus reducing the catalytic efficiency. The agglomeration and pore blockage of the perovskite active agent will lead to a decrease in catalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a graph showing the yield of perovskite active agent loaded coconut shell activated carbon composite materials at different activation temperatures in Examples 1 to 4.
[0031] Figure 2 This is a diagram showing the adsorption effect of the perovskite active agent loaded coconut shell activated carbon composite material at different activation temperatures in Examples 1 to 4.
[0032] Figure 3 This is a graph showing the yield of perovskite active agent loaded coconut shell activated carbon composite materials at different activation times in Examples 5 to 7.
[0033] Figure 4 This is a diagram showing the adsorption effect of the perovskite active agent loaded coconut shell activated carbon composite material at different activation times in Examples 5 to 7.
[0034] Figure 5 This is a diagram showing the adsorption effect of the initial pH of printing and dyeing wastewater on the perovskite active agent loaded coconut shell activated carbon composite material prepared in Example 6.
[0035] Figure 6 This is a diagram showing the adsorption effect of the coconut shell activated carbon prepared in comparative example 1 and the perovskite active agent-loaded coconut shell activated carbon composite material prepared in example 6 under the same conditions. DETAILED DESCRIPTION
[0036] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0037] In the prior art, although a variety of modification methods based on coconut shell activated carbon have been proposed and tried to be applied to the treatment of printing and dyeing wastewater, such as the use of tetrabutyl titanate as a modifier to prepare three-dimensional electrode filling particles modified coconut shell activated carbon (CN202010173132), and the preparation of printing and dyeing wastewater treatment agents by combining phosphoric acid, copper nitrate, cerium nitrate and other modifiers and various additives (CN107758789A), these methods have optimized the treatment efficiency or cost to varying degrees. However, the former increases energy consumption due to the need for an additional electrolysis process, and this restriction weakens its flexibility in practical applications; the latter, due to the wide variety of raw materials and complex ratios, brings challenges to industrial large-scale production, which in turn affects its economy and practicability for widespread promotion.
[0038] In view of the shortcomings of the prior art, the present invention proposes a method for preparing a composite material of perovskite active agent loaded with coconut shell activated carbon, comprising the following steps: using coconut shell as raw material to prepare coconut shell activated carbon; preparing LaCo 1-x Mn xO3, wherein the molar ratio of lanthanum, cobalt and manganese is 1:1-x:x, x is 0-1; LaCo 1-x Mn x O3 is loaded on coconut shell activated carbon to obtain a perovskite active agent loaded coconut shell activated carbon composite material.
[0039] The present invention first uses La, Co and Mn metal salts as raw materials and adopts a sol-gel method to prepare a perovskite active agent; then coconut shell is used as raw material to prepare activated carbon, and the perovskite active agent is loaded on the coconut shell activated carbon by an impregnation method to obtain a perovskite active agent loaded coconut shell activated carbon composite material. Among them, coconut shell, due to its thermal polycondensation reaction characteristics of its lignin component, is converted into a key component of activated carbon during the carbonization process, giving the perovskite active agent loaded coconut shell activated carbon composite material excellent physical and chemical properties. LaCo 1-x Mn x The loading of O3 on the surface of coconut shell activated carbon is efficiently distributed in an amorphous form before reaching saturation coverage, showing extraordinary catalytic activity.
[0040] Compared with the prior art, the preparation method of the perovskite active agent loaded coconut shell activated carbon composite material not only effectively utilizes waste biomass resources and greatly reduces production costs, but also significantly improves the adsorption performance of the perovskite active agent loaded coconut shell activated carbon composite material by introducing perovskite active components, surpassing similar products. At the same time, the preparation method is simple and fast, and the prepared perovskite active agent loaded coconut shell activated carbon composite material has a long cycle life, providing an efficient, economical and environmentally friendly solution for the field of printing and dyeing wastewater treatment.
[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments:
[0042] Example 1
[0043] The preparation method of the composite material of coconut shell activated carbon loaded with a perovskite active agent comprises the following steps:
[0044] S1, the coconut shell raw material is crushed, and then placed in a constant temperature drying oven, and dried at a temperature of 105° C. for 24 h to obtain dry coconut shell.
[0045] S2. Put the dry coconut shell into a crucible, then put the crucible into a horizontal pyrolysis furnace, continuously introduce nitrogen to isolate oxygen, activate at an activation temperature of 700° C. for 30 minutes, and obtain coconut shell activated carbon.
[0046] S3. Weigh lanthanum nitrate hexahydrate, cobalt nitrate hexahydrate, manganese nitrate and citric acid, and dissolve them together in deionized water to obtain a precursor solution; add ammonia water dropwise to the precursor solution, and adjust the pH to 8.5, then put it in a water bath, and continue heating and stirring at 85°C for 5 hours until the precursor solution becomes a viscous gel; place the gel in a muffle furnace, and calcine it at 750°C for 5 hours to obtain a perovskite active agent.
[0047] The molar ratio of lanthanum nitrate hexahydrate, cobalt nitrate hexahydrate and manganese nitrate is 1:0.7:0.3, and the molar ratio of the total molar amount of lanthanum nitrate hexahydrate, cobalt nitrate hexahydrate and manganese nitrate to citric acid is 1:1.5.
[0048] S4, add the 80-mesh coconut shell activated carbon from step 2 to deionized water, stir at 60°C for 0.5h, filter, and rinse with deionized water; repeat the above operation 10 times, and then dry at 100°C for 12h to obtain treated activated carbon;
[0049] LaCo 1-x Mn x The O3 solution was impregnated onto the treated activated carbon, left to stand for 6 hours, and then placed in a constant temperature drying oven at 100°C for 12 hours to obtain a precursor.
[0050] S5. The precursor of step S4 is calcined at 350° C. for 5 h under N2 atmosphere to obtain a composite material of coconut shell activated carbon loaded with a perovskite active agent.
[0051] Example 2
[0052] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 1, except that the activation temperature is increased from 700°C to 800°C.
[0053] Example 3
[0054] The preparation method of the perovskite active agent loaded coconut shell activated carbon composite material is the same as the preparation steps of Example 1, except that the activation temperature is increased from 700°C to 900°C.
[0055] Example 4
[0056] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 1, except that the activation temperature is increased from 700°C to 1000°C.
[0057] The perovskite active agent loaded coconut shell activated carbon composite material is applied to the treatment of printing and dyeing wastewater. 1g / L malachite green solution is used as the simulated printing and dyeing wastewater. After measuring 10mL of malachite green solution, 10mg of perovskite active agent loaded coconut shell activated carbon composite material is added thereto. Then, the solution with the perovskite active agent loaded coconut shell activated carbon composite material is packaged and placed in a constant temperature water bath shaker. It is shaken at a speed of 150rpm and a temperature of 25°C for 24h. The perovskite active agent loaded coconut shell activated carbon composite material is used to adsorb malachite green. After the adsorption is completed, the malachite green solution is filtered using a syringe and a syringe filter, and the absorbance of the obtained filtrate is measured at a wavelength of 618nm using an ultraviolet spectrophotometer. After dilution, the concentration of malachite green in the adsorbed solution is calculated based on the standard curve.
[0058] Figure 1 The yield graph of the composite material of perovskite active agent loaded with coconut shell activated carbon at different activation temperatures of Examples 1 to 4 is as follows: Figure 1 As shown, when the activation temperature is 700°C, the yield is 26.78%. When the activation temperature is increased to 1000°C, the yield decreases to 25.70%. The yield decreases with increasing activation temperature.
[0059] Figure 2 The adsorption effect diagram of the composite material of coconut shell activated carbon loaded with perovskite active agent at different activation temperatures of Examples 1 to 4 is as follows: Figure 2 As shown in the figure, the adsorption amount of coconut shell-based biochar increased from 506.12 mg / g to 624.71 mg / g when the activation temperature increased from 700°C to 1000°C, but then decreased to 604.55 mg / g at an activation temperature of 1000°C.
[0060] Example 5
[0061] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 3, except that the activation time is increased from 30 min to 60 min.
[0062] Example 6
[0063] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 3, except that the activation time is increased from 30 min to 90 min.
[0064] Example 7
[0065] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 3, except that the activation time is increased from 30 min to 120 min.
[0066] Example 8
[0067] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 6, except that in step S3, the gel is placed in a muffle furnace and calcined at 730° C. for 6 hours.
[0068] Example 9
[0069] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 6, except that in step S3, the gel is placed in a muffle furnace and calcined at 780° C. for 4 h.
[0070] Example 10
[0071] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 1, except that in step S3, x is replaced from 0.3 to 0.5.
[0072] Embodiment 11
[0073] The preparation method of the composite material of coconut shell activated carbon loaded with perovskite active agent is the same as the preparation steps of Example 1, except that in step S3, x is replaced from 0.3 to 0.7.
[0074] Embodiment 11
[0075] The preparation method of the composite material of coconut shell activated carbon loaded with a perovskite active agent is the same as the preparation steps of Example 1, except that in step S3, x is replaced from 0.3 to 1, and the perovskite active agent is LaMnO3.
[0076] Example 12
[0077] The preparation method of the composite material of coconut shell activated carbon loaded with a perovskite active agent is the same as the preparation steps of Example 1, except that in step S3, x is replaced from 0.3 to 0, and the perovskite active agent is LaCoO3.
[0078] Comparative Example 1
[0079] A method for preparing coconut shell activated carbon comprises the following steps:
[0080] S1, the coconut shell raw material is crushed, and then placed in a constant temperature drying oven, and dried at a temperature of 105° C. for 24 h to obtain dry coconut shell.
[0081] S2. Put the dry coconut shell into a crucible, then put the crucible into a horizontal pyrolysis furnace, continuously introduce nitrogen to isolate oxygen, activate at an activation temperature of 700° C. for 30 minutes, and obtain coconut shell activated carbon.
[0082] The perovskite active agent-loaded coconut shell activated carbon composite material was applied to the treatment of printing and dyeing wastewater. The printing and dyeing wastewater was simulated with a malachite green solution with an initial concentration of 1g / L. 10mL of malachite green solution was added to 10mg of the perovskite active agent-loaded coconut shell activated carbon composite material. The solution with the perovskite active agent-loaded coconut shell activated carbon composite material was packaged and placed in a constant temperature water bath shaker, and shaken at a speed of 150rpm and a temperature of 25°C for 24h. After the adsorption reaction was completed, the malachite green solution was filtered using a syringe and a syringe filter, and the absorbance of the obtained filtrate was measured at a wavelength of 618nm by an ultraviolet spectrophotometer. After dilution, the concentration of the adsorbed solution was calculated in combination with the standard curve.
[0083] Figure 3 The yield of the composite material of perovskite active agent loaded with coconut shell activated carbon at different activation times in Examples 5 to 7 is shown. Figure 3 As shown, when the activation time was extended from 30 min to 120 min, the yield of biochar first increased from 25.93% to 26.07% and then slightly decreased to 26.06%. When the activation time was 120 min, it increased again to 26.07%.
[0084] Figure 4 The adsorption effect diagram of the composite material of coconut shell activated carbon loaded with perovskite active agent at different activation temperatures in Examples 5 to 7. Figure 4 As shown in the figure, when the activation time is extended from 30min to 120min, the adsorption amount of malachite green solution by the perovskite active agent loaded coconut shell activated carbon composite material increases from 623.62mg / g to 843.68mg / g. When the activation time is 90min, the adsorption amount of biochar is 827.24mg / g, which is similar to the adsorption effect of the perovskite active agent loaded coconut shell activated carbon composite material with an activation time of 120min.
[0085] The adsorption performance under different pH conditions is studied as follows:
[0086] Step 1, using malachite green solution to simulate printing and dyeing wastewater, and adding sodium hydroxide solution dropwise to 1.5 g / L malachite green solution to adjust the pH to 4, 6, 8, 10, and 12 respectively;
[0087] Step 2, take 10 mL of malachite green solutions of different pH values, add 10 mg of perovskite active agent-loaded coconut shell activated carbon composite material to each solution, put it into a constant temperature shaking box, and shake it at 25°C and 150 rpm for 24 hours;
[0088] Step 3: After the adsorption process is completed, the absorbance is measured to determine the adsorption effect.
[0089] Figure 5The figure is a graph showing the adsorption effect of the initial pH of the printing and dyeing wastewater on the perovskite active agent-loaded coconut shell activated carbon composite material prepared in Example 6. Figure 5 As shown in the figure, the adsorption amount of malachite green solution by the perovskite active agent loaded coconut shell activated carbon composite material increases with the increase of pH. When the pH is greater than 8, the adsorption amount of malachite green by the perovskite active agent loaded coconut shell activated carbon composite material tends to be stable, reaching more than 90%. When the pH is less than 6, the adsorption amount of malachite green by the perovskite active agent loaded coconut shell activated carbon composite material is small. With the increase of pH, the adsorption amount of malachite green by the perovskite active agent loaded coconut shell activated carbon composite material increases from 718.63 mg / g at pH = 4.02 to 2174.58 mg / g at pH = 11.96.
[0090] The coconut shell activated carbon prepared in Comparative Example 1 and the perovskite active agent loaded coconut shell activated carbon composite material prepared in Example 6 were respectively applied to the treatment of printing and dyeing wastewater, and the printing and dyeing wastewater was simulated with a malachite green solution with an initial concentration of 1g / L, and 10mL of malachite green solution was respectively placed in two clean reaction containers, and 10mg of perovskite active agent loaded coconut shell activated carbon composite material and 10mg of coconut shell activated carbon were added to the two containers, respectively, and then the two containers were packaged and placed in a constant temperature water bath shock box, and shaken at a speed of 150rpm and a temperature of 25°C for 24h. After the adsorption reaction is completed, the malachite green solution is filtered using a syringe and a syringe filter, and the absorbance of the obtained filtrate is measured at a wavelength of 618nm by an ultraviolet spectrophotometer, and the concentration of the adsorbed solution is calculated after dilution in combination with the standard curve.
[0091] Figure 6 This is a diagram showing the adsorption effect of the coconut shell activated carbon prepared in Comparative Example 1 and the perovskite active agent-loaded coconut shell activated carbon composite material prepared in Example 6 under the same conditions. Figure 6 As shown, the coconut shell activated carbon material loaded with perovskite active agent can effectively improve the adsorption capacity of malachite green, and its malachite green adsorption amount is about twice that of the coconut shell activated carbon in comparative example 1. Under the same adsorption conditions, the adsorption amount of malachite green by the coconut shell activated carbon in comparative example 1 is 1040.79 mg / g, and the adsorption amount of malachite green by the coconut shell activated carbon composite material loaded with perovskite active agent reaches 2174.57 mg / g.
[0092] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a composite material of perovskite active agent loaded with coconut shell activated carbon, characterized in that: The steps include: Coconut shell activated carbon is prepared using coconut shell as raw material; The perovskite active agent LaCo is prepared by sol-gel method using La, Co and / or Mn metal salts as raw materials. 1-x Mn x O3, wherein the molar ratio of lanthanum, cobalt and manganese is 1:1-x:x, x is 0 to 1; LaCo 1-x Mn x O3 is loaded on coconut shell activated carbon to obtain a perovskite active agent loaded coconut shell activated carbon composite material.
2. The method for preparing the composite material of coconut shell activated carbon loaded with perovskite active agent according to claim 1, characterized in that: Perovskite active agent loaded coconut shell activated carbon composite material, LaCo 1-x Mn x The mass percentage of O3 is 0.1wt% to 0.5wt%.
3. The method for preparing the composite material of coconut shell activated carbon loaded with perovskite active agent according to claim 1, characterized in that: The particle size of coconut shell activated carbon is 60 mesh to 100 mesh.
4. The method for preparing the composite material of coconut shell activated carbon loaded with perovskite active agent according to claim 1, characterized in that: The load method is: The coconut shell activated carbon is washed with deionized water and then dried to obtain treated coconut shell activated carbon; LaCo 1-x Mn x O3 is dispersed in deionized water to obtain LaCo 1-x Mn x O3 solution; LaCo 1-x Mn x The O3 solution is impregnated onto the treated coconut shell activated carbon, and after standing and drying, a perovskite activator-loaded coconut shell activated carbon composite material is obtained.
5. The method for preparing the composite material of coconut shell activated carbon loaded with perovskite active agent according to claim 1, characterized in that: Coconut shell activated carbon was prepared according to the following steps: After the coconut shell is dried, it is heated at 700°C to 1000°C for 30min to 120min in a protective atmosphere.
6. The method for preparing the composite material of coconut shell activated carbon loaded with perovskite active agent according to claim 1, characterized in that: LaCo 1-x Mn x O3 was prepared as follows: Mixing citric acid, lanthanum nitrate hexahydrate, cobalt nitrate hexahydrate and / or manganese nitrate in deionized water, and then adjusting the pH to 8-9 with ammonia water to obtain a precursor solution; The precursor solution is heated and stirred at 80°C to 90°C until a viscous gel is obtained; The gel was calcined at 730℃~780℃ for 4h~6h to obtain LaCo 1-x Mn x O3.
7. A composite material of coconut shell activated carbon loaded with a perovskite active agent prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the perovskite active agent loaded coconut shell activated carbon composite material according to claim 7 in the preparation of a malachite green treating agent.
9. The use according to claim 8, characterized in that: The application method is: The perovskite active agent loaded coconut shell activated carbon composite material is added into the printing and dyeing wastewater, shaken and mixed, and the perovskite active agent loaded coconut shell activated carbon composite material is used to adsorb and catalytically degrade malachite green in the printing and dyeing wastewater.
10. The use according to claim 8, characterized in that: The pH value of printing and dyeing wastewater is 4-10.
Citation Information
Patent Citations
Preparation method and application of perovskite type composite oxide catalyst
CN102166517A
Preparation and application of printing and dyeing sewage treatment agent
CN107758789A
Environment pollutant dye adsorbing material
CN110354806A
Biochar-based supported catalyst as well as preparation method and application thereof
CN114849699A
Method for preparing honeycomb ceramic / biochar film / rare earth perovskite monolithic catalyst, and use thereof
WO2023087866A1
